Emergency department utilisation by vulnerable paediatric populations during the COVID‐19 pandemic. (7th August 2020) - Cheek, John A; Craig, Simon S; West, Adam; Lewena, Stuart; Hiscock, Harriet
Abstract: Objective: To determine if changes to community‐based services have effected paediatric ED attendances for mental health issues and neonates during the COVID‐19 pandemic. Methods: Analysis of total presentations, presentations with a mental health diagnoses and presentation of neonates during the early stages of the pandemic compared with the previous year for four Victorian hospitals. Results: There was a 47.2% decrease in total presentations compared with 2019, with a 35% increase in mental health diagnoses and a 2% increase in neonatal presentations. Conclusion: Vulnerable paediatric patients are seeking care elsewhere during the pandemic because of the closure of community services.